How democracies die - Levitsky, Steven; Ziblatt, Daniel, 1972- (Broadway Books, an imprint of Crown Publishing, a division of Penguin Random House, 2019)
"Donald Trump's presidency has raised a question that many of us never thought we'd be asking: Is our democracy in danger? Harvard professors Steven Levitsky and Daniel Ziblatt have spent more than twenty years studying the breakdown of democracies in Europe and Latin America, and they believe the answer is yes. Democracy no longer ends with a bang--in a revolution or military coup--but with a whimper: the slow, steady weakening of critical institutions, such as the judiciary and the press, and the gradual erosion of long-standing political norms. Drawing on decades of research and a wide range of historical and global examples, from 1930s Europe to contemporary Hungary, Turkey, and Venezuela, to the American South during Jim Crow, Levitsky and Ziblatt show how democracies die--and how ours can be saved."--